Pētnieciskie uzdevumi matemātikā 6.klasei skolēna mācīšanās prasmju veicināšanai - Granta, Inguna (Latvijas Universitāte, 2013)
Diplomdarbs „Pētnieciskie uzdevumi matemātikā 6.klasei mācīšanās prasmju veicināšanai” sastāv no 3 nodaļām, secinājumiem un literatūras saraksta. 1. un 2. nodaļā aplūkots mācību process, mācību saturs un mācību saturs 6.klasē, 3.nodaļā apkopoti pētnieciskie uzdevumi 6.klases matemātikas kursā. Diplomdarbā apkopotie rezultāti praktiski lietojami skolēna mācīšanās prasmju veicināšanai 6.klasē.

The diploma thesis "Research tasks in mathematics for promoting pupils’ self – learning skills in Grade 6" consists of 3 chapters, conclusions and literature references. The first and second chapters explore the learning process, educational content in general and the specific education content in Grade 6. The third chapter summarizes research tasks of a mathematics course in Grade 6. The diploma thesis is applicable in the promotion of pupils’ self – learning skills in Grade 6.
Research tasks in mathematics for promoting pupils' learning skills in Grade 6
Keywords: Pedagoģija